An extraordinary case of recurrent stroke, disseminated thrombosis and endocarditis. (4th June 2018) - Thomas, Liza Mariam; Shaikh, Niaz Ahmed; Pradeep, Ranjana
Abstract : A 43-year-old woman with no known cardiovascular risk factors was admitted with a second episode of ischaemic stroke. She was not a known case of connective tissue disease like systemic lupus erythematosus or antiphospholipid syndrome (APS). During the current episode, she was found to have markedly deranged coagulation parameters and laboratory evidence of microangiopathic haemolysis, but no evidence of sepsis or active bleeding. Further investigation revealed multiple organ infarcts. A diagnosis of probable catastrophic APS was made and she improved dramatically with a combination of plasmapheresis, corticosteroids and therapeutic anticoagulation. Serological markers of APS were negative. Her hospital course was complicated by Libman Sacks endocarditis with significant aortic regurgitation that improved markedly with anticoagulation obviating the need for high-risk cardiac surgery. At discharge, she was stable and well and was advised long-term anticoagulation and rheumatology follow-up.